2015
DOI: 10.1007/s00464-015-4474-5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic outcome of skin adhesives versus transcutaneous sutures in laparoscopic port-site wounds: a prospective randomized controlled trial

Abstract: BackgroundIn an elective laparoscopic surgery, the cosmetic outcome becomes increasingly important. We conducted a study to evaluate the cosmetic outcome 3 months after a laparoscopic procedure and compared skin adhesive (SA) versus transcutaneous suture (TS).MethodsA randomized, controlled, prospective study was conducted at a single study centre in Hamburg, Germany. Seventy-seven patients undergoing laparoscopic surgery with two lower abdominal port sites met the study requirements. It was decided randomly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…23 Similarly, several recent trials have demonstrated that wound closure with OCA offers comparable scar cosmesis compared to repair with sutures. [24][25][26][27][28][29] In accord with our results, a 2014 Cochrane review and meta-analysis found that wound closure with tissue adhesives resulted in significantly more episodes of wound dehiscence than sutures. 30 Strengths of this study include its use of a validated scar assessment tool by blinded observers, a priori data analysis, and larger sample size relative to similar published studies.…”
Section: Discussionsupporting
confidence: 82%
“…23 Similarly, several recent trials have demonstrated that wound closure with OCA offers comparable scar cosmesis compared to repair with sutures. [24][25][26][27][28][29] In accord with our results, a 2014 Cochrane review and meta-analysis found that wound closure with tissue adhesives resulted in significantly more episodes of wound dehiscence than sutures. 30 Strengths of this study include its use of a validated scar assessment tool by blinded observers, a priori data analysis, and larger sample size relative to similar published studies.…”
Section: Discussionsupporting
confidence: 82%
“…Cosmetic outcome was also evaluated at the 1-and 4-week visit by POSAS and MHCS (Table 2). Wounds were judged slightly better in the 11.43 (10)(11)(12)(13) .005…”
Section: Resultsmentioning
confidence: 98%
“…Optimal OCA group than in the transcutaneous suture group. Patients' median POSAS was 9.45 (6-11) and 11.43 (10)(11)(12)(13) in the OCA and suture groups, respectively (P = .005), and surgeon's median POSAS was 9.42 (6-11) and 11.48 (10)(11)(12)(13) in the OCA and suture groups, respectively (P = .006). Furthermore, elevated levels of cosmetic were equally reported for all wounds despite of sealing device with no statistical significance between the two groups at the 4-week visit (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies to suggest the efficacy of tissue adhesive comparable to convetional suture have focused on the skin closure of small incisional surgical wound such as laparoscopic port site or thyroidecomty [ 17 , 18 ]. Using tissue adhesives in major surgeries involving long skin incisions was recently founded to be safe in breast surgery and abdominoplasty [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given that scar formation is occurring at this time, the excellent cosmetic outcome achieved after NCBA closure is meaningful. Many studies have reported that tissue adhesives resulted in the same or better cosmetic outcomes and no increase in wound complications compared to suture closure [ 15 , 17 20 ].…”
Section: Discussionmentioning
confidence: 99%